2021
DOI: 10.1021/acs.energyfuels.1c01709
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Physical Property Estimation of Compounds Derived from the Fast Pyrolysis of Lignocellulosic Materials

Abstract: The development of biomass pyrolysis oil refineries is a very promising path for the production of biofuels and bioproducts from lignocellulosic materials. Given that bio-oil is a complex mixture of organic compounds, the production of valuable bioproducts may imply the use of different separation processes, such as distillation, selective condensation, crystallization based on melting points, liquid−liquid extraction or adsorption, and/or upgrading treatments, such as catalytic cracking or hydrodeoxygenation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 92 publications
8
29
1
Order By: Relevance
“…Biomass pyrolysis, as a promising process for producing renewable bio-oil and biochemicals, has received tremendous attention over the past decades. Despite a high yield (60–70 wt.%) of bio-oil from biomass fast pyrolysis, bio-oil suffers from poor quality including high water content, high acidity, high viscosity, and phase instability, which has largely hindered the commercialization of bio-oil production. It is known that the bio-oil quality is largely determined by the composition of condensable volatiles generated during biomass pyrolysis . To develop novel technologies to produce a high-quality bio-oil, it is of critical importance to understand the formation mechanisms of condensable volatiles from biomass fast pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass pyrolysis, as a promising process for producing renewable bio-oil and biochemicals, has received tremendous attention over the past decades. Despite a high yield (60–70 wt.%) of bio-oil from biomass fast pyrolysis, bio-oil suffers from poor quality including high water content, high acidity, high viscosity, and phase instability, which has largely hindered the commercialization of bio-oil production. It is known that the bio-oil quality is largely determined by the composition of condensable volatiles generated during biomass pyrolysis . To develop novel technologies to produce a high-quality bio-oil, it is of critical importance to understand the formation mechanisms of condensable volatiles from biomass fast pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…5−7 It is known that the bio-oil quality is largely determined by the composition of condensable volatiles generated during biomass pyrolysis. 8 To develop novel technologies to produce a highquality bio-oil, it is of critical importance to understand the formation mechanisms of condensable volatiles from biomass fast pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…These results have demonstrated that the heat required for pyrolysis was dependent on the type of feedstock. For the three biomass wastes, Q py for intermediate pyrolysis was slightly lower than for fast pyrolysis of forestry biomass at the same temperature (Fonts et al 2021). The heat required for pyrolysis of biomass waste was also compared to the higher heating value intrinsically contained in the feedstock, here the Q py values have ranged from 4.1-10.4% of higher heating value of the dry feedstock was missing to achieve self-sustaining energy of the pyrolysis process.…”
Section: The Heat Balance Of Intermediate Pyrolysis Processmentioning
confidence: 98%
“…An extra heat transfer to the carrier gas, i.e. nitrogen, in the order of 1.6 MJ/kg feedstock has to be considered (Fonts et al 2021). Including the heating of nitrogen used as a carrier gas, the total heat required for fast pyrolysis was 3 MJ/kg.…”
Section: Introductionmentioning
confidence: 99%
“…Pujro et al 28 have reviewed the various catalytic reactions involved during pyrolysis oil upgrading, with a special emphasis on the transfer of hydrogen, for deoxygenation, which can be potentially donated "in situ" by the molecules (such as alcohols) present in the bio-oils. Fonts et al 29 have proposed a simple but representative composition of a biomass pyrolysis oil, which can be used as a bio-oil surrogate. Then, they have determined selected thermodynamic, physical, and molecular properties of the organic compounds included in the bio-oil surrogate.…”
Section: ■ Pyrolysis Oilmentioning
confidence: 99%